Platelet Pathology in Patients with Chronic Diffuse Liver Diseases with Viral Etiology - Agzamovna Babadjanova, Shaira; Korkmaz, Serdal; Chutbaevna Kurbonova, Zumrad; Sattarovich Babadjanov, Abdumurat; Baxtiyorovna Musayeva, Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
Objective of the research: Study of platelet hemostasis disorders in patients with chronic hepatitis and liver cirrhosis of viral etiology.Materials and methods: The study included 142 patients with chronic diffuse liver diseases, including 80 patients with liver cirrhosis of viral etiology and 62 patients with chronic viral hepatitis of moderate activity.Research results: Hemorrhagic syndrome was expressed in a group of patients with liver cirrhosis of HBV and HBV+HDV etiology in 63.3% and 70.0%, respectively. Hematological and cytomorphological studies of platelets in patients with liver cirrhosis and chronic hepatitis of viral etiology showed significant abnormalities in the amount of blood cells and platelet morphology in liver cirrhosis and minor changes in chronic hepatitis. Liver cirrhosis of viral etiology was accompanied by significant changes in thrombocytopoiesis in the red bone marrow with severe depression of the megakaryocytic lineage and significant abnormal platelet production in the bone marrow.Conclusions: In LC and chronic hepatitis of viral etiology, morphological characteristics of platelets and production of platelets in bone marrow are disturbed, which is the cause of hemorrhagic syndrome in 34.3-11.6% of LC patients in the stage of decompensation and in 9.6-3.1% of patients with chronic viral hepatitis.